MARKETPLACES AS A DIRECTION OF MARKETING SUPPORT FOR THE DEVELOPMENT OF MULTIFUNCTIONAL FARMS IN UKRAINE - SERHIIENKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The consequences of social and technological changes, the crisis caused by war, the criteria of sustainable development, innovation and the digital revolution in the agricultural sector are manifested in improved business models, company positioning, processes and services throughout the agricultural value chain. Agricultural companies at the local level are changing their positioning in order to reach specific target audiences, attract new generations of consumers, quickly adapt to changes in the external marketing environment, and maximize returns in the context of the development of the digital economy and crisis phenomena.The article examines the role of marketplaces as an effective tool for marketing support for the development of multifunctional farms in Ukraine. The influence of electronic platforms on the agricultural sector is analyzed, in particular on the strategies of promoting products, increasing sales and attracting new consumers. The key benefits of using marketplaces are explored, such as access to a wider market, lower advertising costs and the ability to communicate directly with end consumers. In addition, the article highlights the challenges faced by farmers in the transition to online sales and offers recommendations for overcoming them. The conclusions are based on empirical data obtained through sociological surveys and the analysis of successful cases, which emphasizes the importance of adapting business models to modern market conditions. The results of the research can serve as a basis for further scientific developments and practical recommendations for agricultural producers.The uniqueness of local marketplaces is that farmers retain control over the sales process and receive fair payment for their products, while consumers can be sure of the origin of the products while enjoying the best local and seasonal products. The local orientation of the platform not only reduces the environmental footprint, but also strengthens the connection between producers and consumers, opening new market segments and expanding the geography of sales. Further development of marketplaces should be focused on the introduction of new digital marketing tools to attract consumers, increase the attractiveness, transparency and sustainability of the platform for multifunctional farms. This also includes strengthening regional ties in the agricultural market and forming new consumer habits within the framework of the concept of sustainable development.
Keywords: marketplaces; online marketing; e-commerce; finance; business operations; startups; agricultural market; agricultural products; agricultural marketplaces